Laser‐induced Graphene in Facts, Numbers, and Notes in View of Electroanalytical Applications: A Review - Muzyka, Kateryna; Xu, Guobao (Electroanalysis (New York, N.Y.), 2022)
In this review, laser‐induced graphene (LIG) ‐based electrodes are discussed by covering such essential areas, as a characterization of LIG material properties necessary for electroanalysis, including data on LIG sheet resistance, wettability, spatial resolution, electrochemical characteristics, as well as correlations of “process” ‐ “properties” ‐ “electroanalytical characteristics”of LIG‐electrodes. Moreover, typical and innovative LIG‐based electrodes designs for electroanalytical applications, including combined multi‐analyte multimodal wearable sensors, interdigitated electrodes, are shown. The essential data related to LIG in electroanalysis are summarized in tables. The authors also discussed recent LIG‐based electroanalytical applications. Close attention has been paid to LIG glucose sensors and biosensors.